Penggunaan Senjata Api Oleh Petugas Imigrasi dalam Rangka Penegakan Hukum Keimigrasian - Aldi Rizky Setiyawan; Tofik Yanuar Chandra; Hedwig Adianto Mau (Ridwan Institute, 2022)
The purpose of the study is to get an idea of the implementation of firearms use for immigration officers using empirical normative-research methods with a constitutional approach, and a qualitative approach. Result of research has shown that immigration officer, and the civil servant investigator of immigration are the examples of law enforcement officer who have threat in carry out their duties. Therefore, allowed to be equipped with firearms in the performance of his duties as a martial arts device. But, facts in the immigration office (class I) of Tanjung Priok were found that there had been no use of firearms by immigration staff particularly immigration officers, and the civil servant investigator of immigration in performing duties of immigration law enforcement. As a fact there's only one person in the field who has a licensed for ownership firearms. The obstacle faced by immigration officers, and the civil servant investigator of immigration in the use of firearms, namely There is no chief of immigration office policy yet on which to plan the use of service firearms, There is no rule review of the service firearms ordinance in the Directorate General of Immigration, There are no have qualifications immigration officer and the civil servant investigator of immigration yet, are supported to have a permit, and the use of firearms, And facilities for storage, as well as the treatment of firearms.